Theoretical Investigation of Isomerization and Dissociation Reactions in the CF3CH2Cl ⇄ CF2ClCH2F System - Regina, Anitta; Paranjothy, Manikandan (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2025)
Hydrochlorofluorocarbons are an important class of organic compounds having a wide variety of applications despite their hazardous effects on nature. Among these molecules, CF3CH2Cl and its structural isomer CF2ClCH2F were the subject of many experimental and theoretical studies exploring various reaction pathways of their unimolecular dissociation. A commonly observed pathway is 1,2-HX (X = Cl, F) elimination resulting in the formation of alkenes through a four-membered transition state. In earlier studies, it was proposed that the formation of CF2CHF from CF3CH2Cl occurs via 1,1-HCl elimination resulting in CF3CH followed by migration of the F atom between C centers. A chemical activation experimental study indicated that the Cl/F exchange between C centers may play an important role in the dissociation of CF3CH2Cl and CF2ClCH2F. This study pointed toward replacing the earlier mechanism with the Cl/F exchange followed by 1,2-HCl elimination. In the present work, atomistic level mechanisms for the isomerization and dissociation reactions of the CF3CH2Cl ⇄ CF2ClCH2F system were investigated using electronic structure theory, direct dynamics simulations, and Rice-Ramsperger-Kassel-Marcus theory. The dynamics simulations were performed using the global hybrid functional M06-2X with the 6-31+G* basis set in the gas phase. Trajectories were initiated with fixed total energies for the reactants, and product branching ratios were computed. Detailed study of the trajectories revealed that the Cl/F exchange reaction is dominant at low simulation energies, and the traditional mechanism involving the carbene is the most probable reaction pathway at high energies.